Forming Student Social Intelligence Through Islamic Religion Lectures at Public Universities - Asril, Zainal (Khalifa: Journal of Islamic Education, 2021)
Islamic studies in public university are merely learnt by college students during one term, meanwhile, the Islamic studies is indeed expected to form the intellectual, emotional, social, and spiritual intelligences. However, these intelligence’s types are not easy to be reached in a relatively short time since the deep study is required to be done to view the progress. In relation toward this research, the researcher only focuses to the discussion of the achievement aspect of social brilliance after finishing the Islamic studies. This research used the quantitative method by using survey as a rapprochement. The source of the data was taken through questionnaire that was filled in by four hundred students who had accomplished their studies in one of the public universities in Indonesia. The data were then analyzed descriptively by using SPSS 18.0 version. Overall, the research’s result depicted those Islamic studies during study has been able to form six of social intelligence and they are 1) increasing the attitude to help each other, 2) appreciating the other people’s view, 3) behaving well, 4) speaking politely, 5) being able to keep the relationship with new friends, and 6) respecting the older people. From this research, it can be concluded that although the students studied the Islamic studies concisely, otherwise the result showed that the students had righteous impression and it was capable to construct the student’s social intelligence, as it is known that the social intelligence is one of the key success to accomplish the study in university.